Impact of Climate Change and Anthropogenic Activities on Groundwater in Sanjiang Plain - LIU Bo; FAN Chengfang; SHU Longcang; WANG Wenpeng; HU Xin (Guan'gai paishui xuebao, 2022)
【Background and objective】 Sanjiang Plain is located in the northeast Heilongjiang Province, formed by alluvial and diluvial deposits of Heilong, Wusuli River and Songhua Rivers. Its fertile soils make it one of most important grain production bases in China. Irrigation consumes more than 90% of extracted groundwater in these regions. To sustain its groundwater usage, it is important to understand the impact of climate change and androgenetic activities on groundwater. The purpose of this paper is to address this issue. 【Method】 The analysis was based on groundwater dynamics in typical regions across the plain, and the stepwise support vector regression (SVR) was established to simulate groundwater dynamics in non-irrigated season (October to next April) and irrigated season (May to September). Climate change scenarios were taken from the CMIP6 and the change in groundwater extraction for irrigation were applied to evaluate the response of groundwater depth to climate change from 2020 to 2050. 【Result】 From 2001 to 2017, the depth of groundwater table in typical areas had risen at a rate of 0.2 m/a, largely due to precipitation in non-irrigation season and pumping in irrigated season. Compared with 2001—2017, the annual precipitation increased by 26.76 mm under the SSP585 scenario. If groundwater exploitation increased by 5% annually until 2025, the depth of groundwater table would increase by 17.11 cm in irrigation season and decrease by 1.35 cm in non-irrigation season. Under the medium development scenario of SSP245, the annual precipitation may increase by 38.83 mm in average. If the amount of exploitation remains unchanged on average for many years until 2050, groundwater depth will decrease by 9.50 cm in irrigated season and 1.77 cm in non-irrigated season. Under the sustainable development scenario SSP126, the annual precipitation may increase by 26.56 mm in average. If groundwater exploitation is reduced by 5% annually until 2025, the depth of groundwater table will rise by 19.76 cm in irrigated season and 0.92 cm in non-irrigated season. 【Conclusion】 Groundwater exploitation is the dominant determinant of groundwater change in Sanjiang plain, and climate change affects groundwater in non-irrigation season more than in irrigation season. The rational use of groundwater can effectively alleviate continued decline in regional groundwater table. The stepwise modeling we proposed can effectively model annual variation in groundwater budget in irrigated areas, and simulate the response of groundwater to climate change and anthropogenic activities.